"Run-through" training at specialist training year 1 and uncoupled core surgical training for oral and maxillofacial surgery in the United Kingdom: a snapshot survey. Issue 4 (May 2018) - Garg, M.; Collyer, J.; Dhariwal, D.
Abstract: Training in oral and maxillofacial surgery (OMFS) in the UK has undergone considerable changes during the last 10 years, and "core" surgical training has replaced "basic" surgical training. In 2014 a pilot "run-through" training programme from specialist training year one (ST1)-ST7 was introduced to facilitate early entry into the speciality. Run-through training guarantees that a trainee, after a single competitive selection process and satisfactory progress, will be given training that covers the entire curriculum of the speciality, whereas uncoupled training requires a second stage of competitive recruitment after the first one (for OMFS only) or two years of "core" training to progress to higher specialty training. The first two years of run-through training (ST1-ST2) are the same as for core surgical training. Dual-qualified maxillofacial aspirants and those in their second degree course are curious to know whether they should go for the uncoupled core surgical training or the run-through programme in OMFS. The General Medical Council (GMC) has now agreed that run-through training can be rolled out nationally in OMFS. To assess the two pathways we used an online questionnaire to gain feedback about the experience from all OMFS ST3 and run-through trainees (ST3/ST4) in 2016–2017. We identified and contacted 21 trainees, and 17 responded, including seven run-through trainees. Eleven, including five of the run-through trainees, recommended the run-through training programme in OMFS. Six of the seven run-through trainees had studied dentistry first. The overall mean quality of training was rated as 5.5 on a scale 0–10 by the 17 respondents. This survey gives valuable feedback from the current higher surgical trainees in OMFS, which will be useful to the GMC, Health Education England, OMFS Specialist Advisory Committee, and those seeking to enter higher surgical training in OMFS.